Toxicity and Teratogenic Potential of Piplartine from Piper tuberculatum Jacq. during Embryonic Development in Mice (Mus musculus) - Giulliano Rezende Silva; Lívia Thaís Gontijo Miranda; Shirley Aline da Costa Arteaga da Silva; Laise Rodrigues de Andrade; Natanael Carvalho de Souza; Bruno Silva Sá; Elivaldo Ribeiro de Santana; Andreanne Gomes Vasconcelos; Daniel Carneiro Moreira; Aline Pic-Taylor; Alessandra Durazzo; Massimo Lucarini; et al. (MDPI AG, 2024)
Piplartine, also known as piperlongumine, is a natural and biologically active amide alkaloid found in various Piper species within the Piperaceae family. It possesses numerous beneficial properties that can be leveraged in the development of nanotechnological and pharmaceutical products. However, information on the effects of piplartine on mammalian embryonic development is scarce. This study aims to assess the general toxicity and teratogenic potential of piplartine during the embryonic development of mice. Pregnant mice received daily treatments of 25, 50, or 100 mg/kg of piplartine via gavage from the sixth day of gestation (implantation) to the eighteenth. On the eighteenth day, the mice were euthanized, and whole organs, blood samples (for hematological and biochemical analyses), and bone marrow cells (for DNA fragmentation and cell cycle assays) were collected. The uterus was examined for implantation sites and embryo resorptions. Additionally, fetuses were collected to assess for fetal anomalies. Piplartine did not result in maternal or embryo-fetal toxicity, induce fetal anomalies, cause hematological and biochemical alterations, or lead to DNA fragmentation. The oral administration of piplartine is safe and does not exhibit toxicity or teratogenic effects in mice. This finding opens avenues for the development of piplartine-based biotechnological products for therapeutic interventions in disease treatment.